2007
DOI: 10.1111/j.1600-6143.2007.01771.x
|View full text |Cite
|
Sign up to set email alerts
|

Transient Airway Colonization Is Associated with Airway Inflammation After Lung Transplantation

Abstract: Lower airway tract colonization may trigger neutrophil-mediated airway inflammation. We investigated whether transient airway colonization influences airway inflammation and pulmonary function after lung transplantation (LTx). In this retrospective study, stable LTx patients with consecutive broncho-alveolar lavages (BAL), the first colonized and the second noncolonized, were included to create a Pooled group (P, n = 32) and a Gram Negative (GN, n = 14), Gram Positive (GP, n = 9) and Fungi (F, n = 9) subgroup.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
37
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 43 publications
2
37
0
1
Order By: Relevance
“…Our group has previously shown that TNF-a and IL-1b can cause dysregulated wound repair of injured epithelium by accentuating TGF-b1-driven EMT, demonstrating the link between acute inflammation and epithelial remodelling [5]. Previous data from VOS et al [27] suggest that even transient infection with P. aeruginosa in lung transplant recipients is associated with a significant increase in inflammation. We therefore hypothesised that acquisition of P. aeruginosa in the transplanted lung might produce sufficient inflammatory stimulus to accentuate dysregulated repair via EMT in the airway epithelium.…”
Section: Discussionmentioning
confidence: 96%
“…Our group has previously shown that TNF-a and IL-1b can cause dysregulated wound repair of injured epithelium by accentuating TGF-b1-driven EMT, demonstrating the link between acute inflammation and epithelial remodelling [5]. Previous data from VOS et al [27] suggest that even transient infection with P. aeruginosa in lung transplant recipients is associated with a significant increase in inflammation. We therefore hypothesised that acquisition of P. aeruginosa in the transplanted lung might produce sufficient inflammatory stimulus to accentuate dysregulated repair via EMT in the airway epithelium.…”
Section: Discussionmentioning
confidence: 96%
“…2), indicating that lymphoid neogenesis is initiated before the development of OB. Moreover, considering alloantigen-independent inflammatory stimuli such as ischemia-reperfusion injury at the time of transplantation (40), bacterial colonization in airways (41,42), and bile/acid aspiration (43,44) that contribute to OB/BOS, these Ag-independent factors might be enough to activate resident cells such as endothelial cells in airways to initiate lymphoid neogenesis. An interesting question to be answered in the future is how soon such phenotypical changes in the resident cells (e.g., endothelial cells) leading to lymphoid neogenesis start after lung transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…In the present retrospective study, approved by the Ethical Review Board of the University Hospital Gasthuisberg (Leuven, Belgium), freedom of BOS was investigated in colonised and noncolonised double (SS)LTx recipients, transplanted between January 2000 and December 2005, who underwent routine longitudinal follow-up at the outpatient clinic, as previously described [17].…”
Section: Study Populationmentioning
confidence: 99%
“…Colonisation with mucoid or multiple-antibiotic resistant P. aeruginosa or B. cepacia is associated with a worse prognosis, particularly in cystic fibrosis (CF) patients [10][11][12]. It has been extensively shown that colonisation triggers expression of diverse cytokines by structural airway cells, inducing neutrophil recruitment and thereby perpetuating a cycle of airway inflammation and destruction [13][14][15][16][17][18]. However, whether pseudomonal airway colonisation after LTx occurs secondary to the airway remodelling in bronchiolitis obliterans syndrome (BOS), the major cause of late graft failure and death in long-term survivors after LTx [19], or similarly plays a primordial role in its aetiology and progression remains elusive [7,[20][21][22].…”
mentioning
confidence: 99%